Prediction of Aspartate Aminotransferase to Platelet Ratio Index with Size of Esophageal Varices in Liver Cirrhosis - Mandal, Amrendra K; Subedi, Prashant; Paudel, Mukesh Sharma; Thapa, Suman; Kafle, Paritosh; Gayam, Vijay; Khalid, Mazin; Kanth, Rajan; Ray, Neetu M; Ray, Sunil; Gautam, Shristy (Journal of Nepal Health Research Council, 2019)
Background: Liver cirrhosis is one of the major causes of morbidity and mortality. The threatening complication of Liver cirrhosis is variceal bleeding. Early diagnosis and initiation of therapy can reduce mortality associated with variceal bleeding. This study is designed to predict the esophageal varices by non-invasive method using aspartate aminotransferase to platelet count ratio index (APRI).Methods: A total of 100 patients were studied between March 2016 and February 2017 with the diagnosis of Liver cirrhosis admitted at Bir Hospital fulfilling the inclusion and exclusion criteria. Ethical approval was obtained from Institutional review board of National Academy of Medical Sciences.Results: Out of one hundred patients, 80 were males and 20 females. On endoscopy, small varices were present in 28 (28%) patients and large varices in 51(51%) patients. APRI with a cutoff value of 0.908 has sensitivity of 87.3% and specificity of 71.4%, positive predictive value of 92% and negative predictive value of 60% (p=0.001) for the detection of varices.Conclusions: Aspartate aminotransferase to platelet count ratio index can be a useful tool to indirectly predict esophageal varices in a patient with Liver Cirrhosis.Keywords: Aminotransferase; aminotransferase to platelet ratio index APRI; esophageal varices; liver cirrhosis; platelet count.